Optimization of temperature and drying time in the process of making paracetamol tablets using PVP K-25 as a Binder - Yanita Yomberlin Sinta Maria Barangan; Agatha Budi Susiana Lestari (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Wet granulation is a crucial technique in tablet manufacturing as it improves the physical properties of the formulation, such as the flowability and compressibility of paracetamol. One of the critical stages in this process is drying the granules using oven heating. This study aims to optimize the drying temperature and time and evaluate their effects on the physical properties of paracetamol granules and tablets. PVP K-25 was selected as a binder due to its ability to enhance tablet compactness. A full factorial experimental design with two factors and two levels was used, optimizing drying temperature (°C) and drying time (hours) based on the physical properties of granules and tablets. Data were analyzed using ANOVA and Design Expert 13 software to determine the optimal formulation. The results showed that drying temperature, drying time, and their interaction significantly affected the physical characteristics of granules and tablets. The optimal formulation was achieved at 55°C for 4 hours. Formula A (40°C, 6 hours) and Formula B (60°C, 3 hours) demonstrated the best results in producing tablets with desirable physical properties. Thus, optimizing drying temperature and time can enhance the quality of paracetamol granules and tablets.